Dissolution Enhancement of Aceclofenac Drug by Means of Solid Dispersion Technique - AYYAPPAN, T.; VETRICHELVAN, T.; DARLIN QUINE, S. (Asian Journal of Chemistry, 2010)
Aceclofenac is a phenyl acetic acid derivative used in the treatment of pain and inflammation in rheumatoid arthritis, osteoarthritis and ankylosing spondylitis. Aceclofenac is practically insoluble in water. Hence bioavailability is dissolution rate limited. Therefore, solid dispersions of aceclofenac with polyvinyl pyrollidone (PVP K30) were prepared to increase its dissolution rate. Solid dispersions of aceclofenac were prepared using polyvinyl pyrollidone (PVP K30) as water soluble carrier (1:1, 1:2 and 1:3 by weight ratio) employing solvent evaporation method. Dissolution study were carried out using 2 % w/v sodium laurayl sulphate in water as a dissolution medium. Aceclofenac was released at a much higher rate from solid dispersions containing polyvinyl pyrollidone (PVP K30) and physical mixture as compared to that of pure drug powder. Faster dissolution rate was observed in 1:1 drug: carrier ratio. The increase in dissolution rate of the drug may be due to increase wettability, the hydrophilic nature of carrier also possible due to the reduction in drug crystallinity.